Fifty Years of Considering Education: Looking Back and Looking Forward - F. Todd Goodson (Educational Considerations, 2024)
In recognition of 50 years of publication of Educational Considerations by the College of Education at Kansas State University, we invited submissions that examined the scholarship from those 50 years, and we invited forward-looking scholarship that anticipated the next 50 years. I am delighted with the contributions to this issue. We have an analysis of the theme of social justice as it manifested itself across the five decades of the journal’s existence. We have an overview of the representations of school-university partnerships, and we have a contribution focused on the presence of scholarship addressing African education. Finally, we have that forward-facing manuscript that places a post-pandemic lens over the issue of student engagement as we move forward into the next half century.
Keywords: Educational Policy; Education Reform